Ius migrandi: the stated, but unrecognized human right - Costa, Luiz Rosado (Revista Videre, 2020)
Searching for better living conditions, several immigrant workers risk their lives crossing their own country border and entering or remaining in other states irregularly. As there is no recognition of an ius migrandi by the international community, although it is deductible from the Universal Declaration of Human Rights, these immigrants, generally from the poorest strata of the population, remain undocumented, which accentuates their susceptibility to violations of their human rights, not yet totally unrelated to citizenship. Thus, in this descriptive and exploratory research, through the bibliographic and documental method, the recognition of ius migrandi as a human right is what will enable the contact with otherness in an egalitarian way, without the other being considered in a situation of inferiority due to the irregularity of migratory status.